Mewujudkan Sekolah Bebas Bullying dengan Program Pencegahan Kekerasan dalam Proses Pembelajaran - R, Rika Kurnia; Lismayani, Angri; Rusmayadi, Rusmayadi; Musi, Muhammad Akil; Ilyas, Sitti Nurhidayah (KARYA: Journal of Educational Community Service, 2025)
Bullying remains a latent issue at the elementary school level. This community service program aimed to reduce bullying behavior at SD Pemda Makassar by integrating the policy on Violence Prevention and Handling into teaching and learning activities. The population consisted of 43 fifth-grade students, with 15 students purposively selected as peer ambassadors. Core activities included positive discipline training for teachers, the P5 “Friends Without Fear” project, mentoring for Roots peer ambassadors, and the “Counseling Canteen” service for parents. Evaluation results showed significant improvement across four key components of the program. The participants’ average pre-test score was 61.3, which increased to 86.2 in the post-test. These findings confirm that a collaborative strategy involving teachers, students, and parents can create a safer, more positive learning environment that supports the character development of students.